Comparison of adipose stem cells sources from various locations of rat body for their application for seeding on polymer scaffolds. Issue 5 (24th March 2019) - Kurzyk, Agata; Dębski, Tomasz; Święszkowski, Wojciech; Pojda, Zygmunt
Abstract: Adipose tissue yields adult adipose stem cells (ASCs) in large quantities via less-invasive methods. These cells are of interest owing to their modulating properties and paracrine activities, which can be harnessed in regenerative medicine. Many studies on the use of rat fat tissue in an autologous animal model have been conducted; however, the different locations to obtain stromal vascular fraction of rat fat depots have not been fully characterized. The purpose of the current study was to identify optimal source of ASC from various locations of rat body. Animal experiments in vitro revealed that fat depots from cervical fat are an optimal ASC source. A high ASC yield facilitates subsequent studies on autologous transplantation in rats. The secondary objective was to compare the efficiency of osteoinductive media composition and evaluate of osteogenic potential of ASCs for seeding on scaffolds for bone repair. Scaffolds were assessed in vitro, using rat adipose stem cells and three-dimensional (3D) scaffolds comprising polycaprolactone (PCL) or polycaprolactone covered with tricalcium phosphate (PCL + 5%TCP). Seeded ASCs adhere to the surface and migrate to the scaffolds. Upon staining and determining alkaline phosphatase levels, PCL + 5%TCP scaffolds performed better than PCL scaffolds. Furthermore, growth factors such as BMP2 and FGF2 significantly increased ASC mineralization and induced osteogenesis ( p  < 0.05). Our results may help select and develop pre-clinical animal model for confirming the use of ASC, alone or in association with appropriate biomaterials for bone repair.